A new functionalized reduced graphene oxide adsorbent for removing heavy metal ions in water via coordination and ion exchange - Zhang, Chao-Zhi; Chen, Bin; Bai, Yuan; Xie, Jing (Separation science and technology, 2018)
Heavy metal ion pollution has become a serious problem. In this paper, a new type of adsorbent, reduced graphene oxide grafted by 4-sulfophenylazo groups (RGOS), was synthesized to adsorb heavy metal ions in an aqueous solution via two kinds of adsorption modes, ion exchange and coordination. The maximum adsorption capacities of the RGOS for Pb(II), Cu(II), Ni(II), Cd(II) and Cr(III) were 689, 59, 66, 267 and 191 mg/g, respectively. Adsorption equilibrium time of RGOS for heavy metal ions is no more than 10 min. Adsorption mechanism was supposed based on elemental analyses, adsorption data, and Fourier transform infrared spectra.